2020
DOI: 10.3390/molecules25010205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pesticide Residues in Vegetables from the Asir Region, Saudi Arabia

Abstract: This study's aim was to determine the pesticide residues in 10 different vegetable commodities from the Asir region, Saudi Arabia. We evaluated 211 vegetable samples, collected from supermarkets between March 2018 and September 2018, for a total of 80 different pesticides using ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) and gas chromatography-tandem mass spectrometry (GC-MS/MS) after extraction with a multi-residue method (the QuEChERS method). The results were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…Fungal pathogens are the main cause of postharvest losses in fruits and vegetables during storage, shipment, and post-consumer purchase [1,2]. In most crops, the pre and/or postharvest applications of synthetic fungicides have been the main approach used to control decay [3]. Nevertheless, chemical-based control approaches have been under mounting scrutiny by the public and regulatory authorities due to their negative effects on human and animal health, as well as the environment in general [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal pathogens are the main cause of postharvest losses in fruits and vegetables during storage, shipment, and post-consumer purchase [1,2]. In most crops, the pre and/or postharvest applications of synthetic fungicides have been the main approach used to control decay [3]. Nevertheless, chemical-based control approaches have been under mounting scrutiny by the public and regulatory authorities due to their negative effects on human and animal health, as well as the environment in general [3].…”
Section: Introductionmentioning
confidence: 99%
“…In most crops, the pre and/or postharvest applications of synthetic fungicides have been the main approach used to control decay [3]. Nevertheless, chemical-based control approaches have been under mounting scrutiny by the public and regulatory authorities due to their negative effects on human and animal health, as well as the environment in general [3]. This concern has been the main driving force of research to identify effective and more eco-friendly methods for the management of postharvest fungal diseases [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Again pyriproxyfen was not found [50]. Ten different vegetable commodities from the Asir region (Saudi Arabia) were evaluated for their pesticide contamination [51]. In this context, 211 samples were collected from supermarkets in which 80 pesticides (including pyriproxyfen) were analyzed.…”
Section: Residues In Fruits and Vegetablesmentioning
confidence: 99%
“…On the 22 potato samples analyzed, pyriproxyfen was also found twice with concentrations of 0.013 and 0.026 mg/kg. Unfortunately, the LOD and LOQ values were not specifically given for pyriproxyfen [51]. Two hundred date (Phoenix dactylifera var Sukkari) samples (1-2 kg each) were collected from large markets in the Al-Qassim region in Saudi Arabia during 2016 to evaluate their potential contamination in pesticides [52].…”
Section: Residues In Fruits and Vegetablesmentioning
confidence: 99%
“…As the use of fungicides in agriculture has gradually increased, the problems they cause have also attracted worldwide attention. 9 Because of the high toxicity and long-term persistence of fungicides, they can often pollute the environment through a variety of ways, including spraying, soil seepage, and storage and discharge of wastewater, which may cause pollution of the ground and surface water 10 and cause public health problems. 11 In addition, studies have reported that Met may have an effect on mammalian metabolic mechanisms; 12 therefore, the abuse of fungicides also poses a potential risk to wildlife and human health.…”
Section: Introductionmentioning
confidence: 99%